2004
DOI: 10.1074/jbc.m401352200
|View full text |Cite
|
Sign up to set email alerts
|

The 3′-Untranslated Region of the β2-Adrenergic Receptor mRNA Regulates Receptor Synthesis

Abstract: ␤ 2 -Adrenergic receptors (␤ 2 -ARs) are low abundance integral membrane proteins that mediate the effects of catecholamines at the cell surface. Post-transcriptional regulation of ␤ 2 -AR is dependent, in part, on sequences within the 5-and 3-untranslated regions (UTRs) of the receptor mRNA. In this work, we demonstrate that 3-UTR sequences regulate the translation of the receptor mRNA. Deletion of the 3-UTR sequences resulted in 2-2.5-fold increases in receptor expression. The steadystate levels of ␤ 2 -AR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 53 publications
4
34
0
1
Order By: Relevance
“…For the M 1 -muscarinic receptor, an Ϸ260-bp region in the 3Ј UTR, thought to form a stable stem-loop, is critical for mRNA stability (32). For the ␤ 2 AR subtype, 3Ј UTR sequences have been shown to negatively regulate translation of the receptor (33)(34)(35). T cellrestricted intracellular antigen-1 is one RNA binding protein that binds to ␤ 2 AR 3Ј UTR and acts to repress expression at the translational level (35).…”
Section: Variation Of the ␣2aar Gene Alters Transcript And Protein Exmentioning
confidence: 99%
“…For the M 1 -muscarinic receptor, an Ϸ260-bp region in the 3Ј UTR, thought to form a stable stem-loop, is critical for mRNA stability (32). For the ␤ 2 AR subtype, 3Ј UTR sequences have been shown to negatively regulate translation of the receptor (33)(34)(35). T cellrestricted intracellular antigen-1 is one RNA binding protein that binds to ␤ 2 AR 3Ј UTR and acts to repress expression at the translational level (35).…”
Section: Variation Of the ␣2aar Gene Alters Transcript And Protein Exmentioning
confidence: 99%
“…In contrast, when these cells were transfected with GFP NLS / myr without ␤ 2 -AR 3Ј-UTR, the GFP distribution was localized to the perinuclear region of the cells suggesting an important role for the receptor 3Ј-UTR sequences in limiting the distribution of GFP to the cell periphery. In addition, as expected from the inhibitory effect of ␤ 2 -AR 3Ј-UTR on translation (16,17), the fusion of ␤ 2 -AR 3Ј-UTR to GFP caused a reduction in GFP expression. We isolated heavy (plasma membrane) and light membrane fractions from HuR knockdown and control cells and measured the distribution of ␤ 2 -AR by radioligand binding in these fractions.…”
Section: Shrna-mediated Knockdown Of Hur Reduces Steady Statementioning
confidence: 98%
“…We recently reported that cellular expression of ␤ 2 -AR is suppressed at the translational level by 3Ј-untranslated region (UTR)-binding proteins (16,17). The current study was designed to address the importance of translational silencing and mRNA localization in ␤ 2 -AR trafficking to the plasma membrane.…”
Section: G Protein-coupled Receptors (Gpcr)mentioning
confidence: 99%
See 2 more Smart Citations